Haemostatic safety of a unique recombinant plasmin molecule lacking kringles 2–5 - Marder, Victor J.; Manyak, Steve; Gruber, Theresa; Goyal, Abha; Moreno, Guillermo; Hunt, Jennifer; Bromirski, John; Scuderi, Philip; Petteway, Stephen R., Jr; Novokhatny, Valery (Thrombosis and Haemostasis, 2010)
We previously demonstrated a significant margin of haemostatic safety for full-length plasmin in comparison with tissue plasminogen activator (t-PA). We now report studies that compare haemostatic safety of full-length plasmin with a novel recombinant plasmin derivative, (Δ K2–5) plasmin, consisting of kringle 1 linked to the serine protease domain of plasmin. Agent was administered intravenously in a randomised, blinded manner in a rabbit model of fibrinolytic haemorrhage. A dose-related decrease in α2-antiplasmin, factor VIII, and fibrinogen followed administration of 1.8, 2.7, 3.7 and 4.6 mg/kg of (Δ K2–5) plasmin, with nadir fibrinogen concentrations of 65%, 40%, 30%, and 0% of initial levels, respectively. Mean primary bleeding time was undisturbed at 1.8 mg/kg (2.2 ± 0.7 minutes), minimally prolonged at 2.7 or 3.7 mg/kg (5 ± 2.9 and 4.4 ± 2.2 minutes), and prolonged at the purposefully toxic 4.6 mg/kg dose (12.8 ± 18.8 minutes). Equimolar amounts of (Δ K2–5) plasmin and full-length plasmin had equal in vitro clot lysis efficacy, but in the bleeding model, (Δ K2–5) plasmin showed better haemostatic competency than full-length plasmin. This safety advantage may be explained by higher residual amounts of plasma fibrinogen in animals given (Δ K2–5) plasmin rather than full-length plasmin. We demonstrate that a unique recombinant plasmin mutant, (Δ K2–5) plasmin, possesses an advantage in hemostatic safety over an equimolar amount of full-length plasmin.
Keywords: Plasmin; recombinant derivative; haemostasis